2018
DOI: 10.25251/skin.2.supp.68
|View full text |Cite
|
Sign up to set email alerts
|

Short- and Long-Term Efficacy and Safety of Glycopyrronium Cloth for the Treatment of Primary Axillary Hyperhidrosis: Post Hoc Pediatric Subgroup Analyses from the Phase 3 Studies

Abstract: not available. Disclosures: Study sponsored by Dermira Inc. Copyright 2018 SKIN

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…A limitation of these studies is the relatively short duration compared to the chronic nature of primary hyperhidrosis. Results from the long‐term open‐label extension of these trials have been reported, and safety findings from the pediatric subgroup are consistent with the results provided here from the double‐blind trials …”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…A limitation of these studies is the relatively short duration compared to the chronic nature of primary hyperhidrosis. Results from the long‐term open‐label extension of these trials have been reported, and safety findings from the pediatric subgroup are consistent with the results provided here from the double‐blind trials …”
Section: Discussionsupporting
confidence: 84%
“…Results from the long-term open-label extension of these trials have been reported, and safety findings from the pediatric subgroup are consistent with the results provided here from the double-blind trials. 23,24 Despite therapeutic options for axillary hyperhidrosis, patients generally remain dissatisfied with treatment. 6,25 GT was FDAapproved in June 2018 for patients ≥ 9 years with primary axillary hyperhidrosis, representing the first approved treatment to include pediatric patients.…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy of glycopyrronium tosylate in children aged 9 to ≤ 16 years of age was generally similar to that seen in older patients (> 16 years of age) in subgroup analyses of data from the double-blind trials (Table 2) and ARIDO [14, 17]. At week 4, children showed improvements in ASDD/ASDD-C severity of sweating response rate (Table 2), sweat production (Table 2), HDSS response rate (Table 2) and quality of life (DLQI/CDLQI) with glycopyrronium tosylate relative to vehicle that were generally consistent with those seen in older patients [16].…”
Section: What Is the Efficacy Of Glycopyrronium Tosylate In Primary Amentioning
confidence: 63%
“…At week 4, children showed improvements in ASDD/ASDD-C severity of sweating response rate (Table 2), sweat production (Table 2), HDSS response rate (Table 2) and quality of life (DLQI/CDLQI) with glycopyrronium tosylate relative to vehicle that were generally consistent with those seen in older patients [16]. As was the case in the overall population, improvements in disease severity, sweat production and quality of life were maintained over 44 weeks of open-label treatment in children [14, 17]. The benefits of glycopyrronium tosylate over vehicle treatment for primary axillary hyperhidrosis were also generally consistent across subgroups based on location of hyperhidrosis [multifocal (glycopyrronium tosylate applied to axillae only) vs. axillary], receipt of prior treatment, gender, race (white vs. non-white) and body mass index in ATMOS-1 and ATMOS-2 (pooled analysis) [18].…”
Section: What Is the Efficacy Of Glycopyrronium Tosylate In Primary Amentioning
confidence: 91%
See 1 more Smart Citation